PEMANFAATAN KUNYIT MENJADI MINUMAN SERBUK INSTAN DI DESA PAKRAMAN PAU KECAMATAN BANJARANGKAN KLUNGKUNG - PUTU LAKUSTINI CAHYANINGRUM; IDA BAGUS PUTRA SUTA; SANG AYU MADE YULIARI (JURNAL SEWAKA BHAKTI, 2019)
Pakraman Pau Village is one of the villages located in Banjarangkan District, Klungkung Regency, Bali Province. As one of the developing villages in Klungkung which is rich in herbal plants. Many herbal plants are planted on farms and in the homes of residents, especially turmeric. Utilization of turmeric has not been processed optimally, especially in the area of ​​increasing health and added value in helping to improve the family economy. Previously, Pakraman Pau villagers used turmeric only as a kitchen spice and were used as a loloh for health drinks. Therefore, the need for processing with other forms and methods to be more practical and easy to consume can even increase the family's economic income. One of them is the use of turmeric into instant powder drinks with high economic value. The method used was socialization and counseling on the use of Turmeric, a Turmeric Processing Demo into Instant Powder Drinks and evaluation of activities. The results showed that Pakraman Pau villagers could increase their knowledge, understanding, and skills about using turmeric as an instant powder drink to maintain family health and could be a business opportunity for PKK mothers to help improve the family's economy